2016
DOI: 10.1155/2016/4987526
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Implant Collar Surfaces for Marginal Bone Loss: A Systematic Review and Meta-Analysis

Abstract: Background. It is important to understand the influence of different collar designs on peri-implant marginal bone loss, especially in the critical area. Objectives. The purpose of the present systematic review and meta-analysis was to compare dental implants with different collar surfaces, evaluating marginal bone loss and survival rates of implants. Methods. Eligibility criteria included clinical human studies, randomized controlled trials, and prospective and retrospective studies, which evaluated dental imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 53 publications
2
34
1
Order By: Relevance
“…Ad‐hoc analyses did not reveal differences between the smooth group and rough group. Other studies, however, reported significantly more marginal bone loss around implants with a smooth neck compared to a rough neck . These studies mainly investigated posterior implants placed in the lower jaw and it is, therefore, questionable whether these results can be compared with our findings.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Ad‐hoc analyses did not reveal differences between the smooth group and rough group. Other studies, however, reported significantly more marginal bone loss around implants with a smooth neck compared to a rough neck . These studies mainly investigated posterior implants placed in the lower jaw and it is, therefore, questionable whether these results can be compared with our findings.…”
Section: Discussioncontrasting
confidence: 59%
“…Other studies, however, reported significantly | 721 more marginal bone loss around implants with a smooth neck compared to a rough neck. 7 These studies mainly investigated posterior implants placed in the lower jaw and it is, therefore, questionable whether these results can be compared with our findings. It might be that implants in our study were placed deeper in order to create proper emergence profile, which is essential in the esthetic zone.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…A systematic review reported that marginal bone resorption takes place irrespectively on the implant neck configuration [9]. Nevertheless, roughness and micro-threads at the implant neck contribute to marginal bone preservation [10][11][12][13][14]. Few studies have compared the effect of implant surface configurations and geometries on the peri-implant healing process at implants placed immediately into extraction sockets [15,16].…”
Section: Introductionmentioning
confidence: 99%